2022
DOI: 10.32598/jhnm.32.2.2173
|View full text |Cite
|
Sign up to set email alerts
|

Iranian Nurses' Attitudes and Readiness for Nurse Prescribing: A Cross Sectional Study

Abstract: Introduction: Since prescribing is a new subject in the nursing profession, it is necessary to assess nurses' attitudes to and readiness for this new responsibility. Objective: This study aimed to investigate nurses' attitudes to and readiness for nurse prescribing in teaching hospitals of Tabriz City, Iran. Materials and Methods: This cross-sectional analytical study was conducted on 335 nurses working in the hospitals of Tabriz from June to October 2019. The participants were selected with a stratified rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Meanwhile, healthcare institutions must recognize the limitations of novice nurses and support their competent acclimation to the provider role. Tese results, similar to the study by Babaei et al [22], found that there was a positive and signifcant correlation between nurses' attitudes and readiness. In addition, Ahmadi et al [23] recommended that the clinical preparation of nursing students during the internship program enhances clinical readiness in internships.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, healthcare institutions must recognize the limitations of novice nurses and support their competent acclimation to the provider role. Tese results, similar to the study by Babaei et al [22], found that there was a positive and signifcant correlation between nurses' attitudes and readiness. In addition, Ahmadi et al [23] recommended that the clinical preparation of nursing students during the internship program enhances clinical readiness in internships.…”
Section: Discussionsupporting
confidence: 89%
“…Further, nurses were well situated to respond to patient changes quickly and appropriately especially in the absence of physicians [ 13 ]. In the study of Babaei et al (2022) which aimed to determine the attitude and readiness of Iranian nurses towards nurse prescribing, the results showed that nurses had a good preparation and attitude towards nurse prescribing [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, like other countries, there are independent and dependent prescribing practices, but the quality and manner of prescribing is greatly different in Iran because nurse prescribing is carried out illegally and, in some cases, secretly [14]. In the study by Babaie et al [15] that aimed to determine the attitude and readiness of Iranian nurses toward nurse prescribing, the results showed that nurses had a good preparation and attitude toward nurse prescribing [15].…”
Section: Introductionmentioning
confidence: 99%